Analisis KI-3 Kurikulum 2013 Kimia pada Kelas X SMA - Yusi Andayani; Eka Yusmaita (Edukimia, 2019)
The content standard has several components, including the level of competence, core competency (KI), basic competency (KD) and the scope of the material. The content standard always changes according to the needs of curriculum to be applied. The purpose of this research is to analyze the formula of KI-3 based on Bloom taxonomic revision. This is one of the basic frameworks in curriculum preparation which starts from the cognitive and knowledge dimensions. The type of this research is descriptive qualitative. Data collection techniques is using library research. The data source used Permendikbud No. 37 of 2018. The formula KI-3 was analyzed based on knowledge activities, types of knowledge and scientific attitudes. The results of KI-3 formulation at 1st grade of senior high school obtained 36 components of KI-3.